KONSEP KHILAFAH DAN KESALEHAN LINGKUNGAN DALAM TRADISI ISLAM - Joko Christanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2012)
This article describes and reveals the concept of khali>fah in Islamas the basic in natural exploration. This concept brings man into the highestdegree among God’ creatures. Man’s responsibility is as the God’s representativein the earth. Man should be inspired by some of God’s namesuch as arranger (mudabbir), protector (ha>fidz), and educator (murabbi).The data are collected and documented from the main source; al-Qur’anand al-Sunnah and it is analyzed with bayani and philosophical approach.This article shows that khali>fah concept in Islam is based on ila>hiyyahand daru>riyyah (need) insa>niyyah transcendence. The environmental damageis caused by the unbalanced situation, man just focuses on the secondpoint.